FAKTOR RISIKO PAJANAN PESTISIDA TERHADAP KEJADIAN KERACUNAN PESTISIDA PADA PETANI DI JAWA TENGAH (STUDI LITERATUR HASIL-HASIL PENELITIAN DI FKM UNDIP) - Mukadar, Lilis Afriyani; Sulistyani, Sulistyani; Joko, Tri (Fakultas Kesehatan Masyarakat, 2018)
: Pesticides are one of the hazardous and toxic materials used in the world of agriculture as pest control on plants. In fact, the use of pesticides continuously and in large quantities will have a negative impact on the environment and also have an impact on human health. This study aims to determine the risk factors for exposure to pesticides to public health by utilizing secondary data in the form of research journals. This research is a quantitative descriptive study with a Comparative Study approach. The population in this study were all journals related to risk factors for pesticide exposure to health from the online library of the Public Health Faculty of Diponegoro University with a sample of 5 research journals focused on Pesticide Exposure Risk Factors to Pesticide Poisoning. The data obtained were analyzed by univariate. The results of the data analysis showed that there were 3 locations in Central Java which were used as research sites, namely in Magelang Regency, Brebes Regency and Semarang Regency, using the Observational Analytical type and the Cross Sectional approach in each study. In the data analysis section the researchers tended to use 2 types of data analysis namely data analysis in Univariate and Bivariate. The most widely used risk factors as research variables are knowledge factors, length of work, years of service, use of PPE and pesticide mixing. From this study it can be concluded that the use of research variables has not varied enough because it only uses variables that have existed before. The next researcher is expected to be able to present new variables that are indicated to affect the occurrence of pesticide poisoning but are minimally included in the study.